Phase- and morphology-controlled MnO2: Its synthesis and influence on the electrochemical performance of spinel LiMn2O4 cathode materials - Young Ji Park; Sang Hyo Jeong; Younki Lee; Tae Wook Kang; Sun Woog Kim (Electrochemistry Communications)
In this study, MnO2 was synthesized via a hydrothermal method using four different oxidizing agents: KMnO4, K2S2O8, KClO3, and (NH4)2S2O8. The KMnO4 precursor led to the formation of aggregated α-MnO₂, while K2S2O8 produced a mixed phase of α- and γ-MnO2. (NH4)2S2O8 promoted the formation of γ-MnO2 at lower temperatures and induced a structural transition to β-MnO2 at elevated temperatures. Among the lithium precursors investigated, LiOH was found to be the most effective in preserving the spherical morphology of LiMn2O4 during synthesis. Electrochemical measurements revealed that the LiMn2O4 sample synthesized from γ-MnO2 exhibited the highest charge capacity of 132.59 mAh∙g−1, while the α-MnO2-based LiMn2O4 demonstrated the best stability. These results indicate that the initial MnO2 phase significantly influences the electrochemical performance of the resulting spinel cathode.